Pengaruh Profitabilitas Dan Liabilitas Terhadap Harga Saham Dengan Kebijakan Dividen Sebagai Variabel Intervening Pada Sektor Energi Yang Terdaftar Di BEI Periode 2020-2024 - Dona Meidini; Fitri Yeni; Resyelly Viona (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the effect of profitability and liabilities on stock prices through dividend policy as an intervening variable in energy sector companies listed on the Indonesia Stock Exchange for the 2020-2024 period. The research population consisted of all energy sector companies listed on the IDX, with a sample of 18 companies selected using purposive sampling method. The data used were secondary data in the form of annual financial reports obtained from the official IDX website. Data analysis techniques used path analysis with SPSS version 25 software. The results showed that profitability significantly influenced dividend policy with a t-value of 3.712 > t-table 1.987 and significance of 0.000 < 0.05. Meanwhile, liabilities did not significantly influence dividend policy with a t-value of -0.427 < t-table 1.987 and significance of 0.670 > 0.05. Profitability significantly influenced stock prices with a t-value of 5.011 > t-table 1.987 and significance of 0.000 < 0.05. However, liabilities did not significantly influence stock prices with a t-value of -0.468 < t-table 1.987 and significance of 0.641 > 0.05. Dividend policy also did not significantly influence stock prices with a t-value of 0.047 < t-table 1.987 and significance of 0.962 > 0.05. The mediation test results showed that dividend policy was unable to mediate the effect of profitability or liabilities on stock prices. The coefficient of determination (R²) value in the first equation was 0.863, indicating that 86.3% of the variation in dividend policy could be explained by profitability and liabilities, while in the second equation the R² value was 0.707, indicating that 70.7% of the variation in stock prices could be explained by profitability, liabilities, and dividend policy. This study implies that investors in the energy sector pay more attention to company profitability as an indicator of fundamental performance in investment decision-making compared to dividend policy.